1997
DOI: 10.1897/1551-5028(1997)016<1954:sbeaan>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Serum B Esterases as a Nondestructive Biomarker in the Lizard Gallotia Galloti Experimentally Treated With Parathion

Abstract: Abstract-Lizards (Gallotia galloti) were given either single or consecutive acute oral treatments of the organophosphorus (OP) insecticide parathion in two different experiments. Brain, serum, and liver microsomal esterase activities and liver microsomal monooxygenase activities were measured 6 and 24 h after the single acute treatment at each of four different doses (Experiment 1) or periodically up to 72 d after a number of consecutive acute treatments at two different doses (Experiment 2). Inhibition of ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Serum BChE activity is suggested to be a better biomarker than serum AChE activity for assessing exposure to anti‐ChE pesticides. The high activity (on BuSCh) of serum BChE with respect to AChE, together with the previously reported [26] response to the inhibitory effect from OPs (high sensitivity and slow recovery rate after acute OP exposure), justify the use of serum BChE activity as an acceptable biomarker of pesticide exposure in G. galloti .…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Serum BChE activity is suggested to be a better biomarker than serum AChE activity for assessing exposure to anti‐ChE pesticides. The high activity (on BuSCh) of serum BChE with respect to AChE, together with the previously reported [26] response to the inhibitory effect from OPs (high sensitivity and slow recovery rate after acute OP exposure), justify the use of serum BChE activity as an acceptable biomarker of pesticide exposure in G. galloti .…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, optimal conditions for ChE measurements in G. galloti are in the pH range of 7.5 to 8.0 and the substrate concentrations of 5 mM (serum and brain AChE) or 10 mM (serum BChE) (Table 2). Although not examined in this study, an incubation temperature of 25°C was considered as optimal for ChE measurements, as previously reported for this lizard species [26]. Likewise, data on the most favorable conditions for determining ChE activity in some species of aquatic invertebrates and fish are also reported in Table 2 for comparison.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition to some older studies, all of the recent studies on the effects and accumulation of pesticides on lizards have been conducted in Australia, Africa, and Europe [7,10,15, 25,26]. These recent studies are promising because the sublethal effects of organic contaminants were studied, and these effects were linked to exposure concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, laboratory studies with Gallotia galloti found that carboxylesterase activity was inhibited for a longer duration than was brain acetylcholinesterase activity following parathion exposure, suggesting that carboxylesterase activity was a superior biomarker (Sanchez et al 1997b). However, field studies with Gallotia galloti in the Canary Islands found that carboxylesterase and acetylcholinesterase activity were essentially equally inhibited following exposure to the OP trichlorphon, whereas butyrylcholinesterase activity was only slightly affected (Fossi et al 1995).…”
Section: Applications In Terrestrial Organismsmentioning
confidence: 99%